The Rise and Fall of Modern Political Space - Galli, Carlo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2015)
In order to analyze the rise and fall of modern political space, it is necessary to understand how space matters in political thought and in politics, starting from an exposition of what is meant with the concept of “implicit space”.This is the aim of my paper, which is based on the ideas I developed in Political Spaces and Global War (2010).